2012
DOI: 10.1177/105268461202200109
|View full text |Cite
|
Sign up to set email alerts
|

Managing Educational Champions: Entrepreneurship in Schools

Abstract: This study explores how educational champions—teachers who initiate unsolicited innovation—construct their entrepreneurial endeavors while interacting with principals’ management styles and how that interaction influences the sustainability of teachers’ initiatives. Through semistructured interviews ( N = 71) and analysis anchored in grounded theory, champions revealed three entrepreneurship strategies: semiautonomous entrepreneurship while interacting with a facilitative managerial style, loosely coupled entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 95 publications
0
24
0
Order By: Relevance
“…The majority of informants were students and teachers/educators. Only a few studies focused on school leadership, the principal's role or function related to pedagogical entrepreneurship, or on the implementation of entrepreneurial strategies in schools (Eyal and Yosef-Hassidim 2012;Leffler 2006;Mahieu 2006; Sjøvoll and Pedersen 2014).…”
Section: Overview Of Research Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of informants were students and teachers/educators. Only a few studies focused on school leadership, the principal's role or function related to pedagogical entrepreneurship, or on the implementation of entrepreneurial strategies in schools (Eyal and Yosef-Hassidim 2012;Leffler 2006;Mahieu 2006; Sjøvoll and Pedersen 2014).…”
Section: Overview Of Research Methodsmentioning
confidence: 99%
“…However, several studies reported confusion about the concept of entrepreneurship among representatives at several levels of the school systems. On several occasions, entrepreneurial and traditional schools were interpreted in terms of a dichotomy (Dahlstedt and Hertzberg 2012;Eyal and Yosef-Hassidim 2012;Leffler 2006), and it was reported that the introduction of an entrepreneurial approach requires fundamental change and development. Therefore, statements of requirements were often supported by referring to societal and economic challenges manifested in policy documents.…”
Section: Research Challenges In Pedagogical Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure has been used before (e.g. Eyal & Yosef‐Hassidim, ). First, the head nurse and deputy nurse were asked to name any nurse involved in initiating and implementing innovation beyond the direct, routine treatment of the patients he or she is responsible for.…”
Section: The Studymentioning
confidence: 99%